2017
DOI: 10.1016/j.hpb.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Does revision of resection margins based on frozen section improve overall survival following pancreatoduodenectomy for pancreatic ductal adenocarcinoma? A meta-analysis

Abstract: IOFS-based revision of R1 pancreatic resection margin does not improve OS, even when it results in an R0 margin. This suggests that any benefit of margin revision based on FS is over-ridden by markers of more advanced or aggressive disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…Although the majority of previously published studies support the findings of the present study, there have been some conflicting results, which have suggested more aggressive surgical interventions should be performed to achieve an R0 margin [ 18 , 28 , 29 ]. Fatima et al reported that the OS rates of patients who were R1 frozen section-positive but became R0 after additional resections were similar to those of patients who were R0 intra-operatively and that these rates were significantly higher than those of patients who were R1 in paraffin section analysis [ 10 ].…”
Section: Discussionsupporting
confidence: 61%
“…Although the majority of previously published studies support the findings of the present study, there have been some conflicting results, which have suggested more aggressive surgical interventions should be performed to achieve an R0 margin [ 18 , 28 , 29 ]. Fatima et al reported that the OS rates of patients who were R1 frozen section-positive but became R0 after additional resections were similar to those of patients who were R0 intra-operatively and that these rates were significantly higher than those of patients who were R1 in paraffin section analysis [ 10 ].…”
Section: Discussionsupporting
confidence: 61%
“…Re-resection of intraoperatively detected positive resection sites has been demonstrated to have only a marginal influence on survival, which further highlights the importance of primary margin negative resections (R0CRM-) in PDAC surgery [32][33][34]. The persistently high rates of margin positive resections suggest that the necessary extent of surgery has not been achieved over the past decade [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Comments: Several reports have compared the survival of patients between those who have undergone an additional resection and finally have negative pancreatic resection margin and those who have not undergone additional resection in spite of positive resection margin or who have positive resection margin after additional pancreatic resection [ 78 - 85 ]. Except for two studies that failed to perform survival analysis due to the small number of included patients [ 79 , 82 ], the remaining retrospective studies showed controversial results in survival outcome [ 78 , 80 , 81 , 83 ].…”
Section: Recommendations ( Table 3 )mentioning
confidence: 99%